Respuestas
Respuesta dada por:
0
(x-1) (x-5) = x² - x - 5x +5 = x² - 6x + 5
Respuesta dada por:
2
Aplicar productos notables
(x - 1)( x - 5) =
1ro Multiplicas x . x = x²
2do sumas - 1 - 5 = -6 y le agregas la variable x = - 6x
3ro Multiplicas (-1)( -5) = +5
Queda:
(x - 1)(x - 5) = x² - 6x + 5
(x - 1)( x - 5) =
1ro Multiplicas x . x = x²
2do sumas - 1 - 5 = -6 y le agregas la variable x = - 6x
3ro Multiplicas (-1)( -5) = +5
Queda:
(x - 1)(x - 5) = x² - 6x + 5
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 9 años
hace 9 años